Devoted to the Master: The Case of Ibn Hajar and Ibn Khidr as an Example of Patronage Among Scholars During the Mamluk Dynasty - Halit Özkan (İslam Tetkikleri Dergisi)
In this study, I examine the use and function of the patronage system by and among scholars during the Mamluk dynasty with the example of Ibn Hajar al-Asqalānī’s famous disciple and lifelong devotee Ibn Khidr al-Qusūrī. Based on tabaqāt, biographic and autobiographic sources of the period, as well as the extant manuscripts of Ibn Hajar’s works that were copied during his lifetime, I examine how Ibn Khidr, who was a very important figure of the time in Ibn Hajar’s circle but has now been practically forgotten, helped his master in various matters and was protected by his master in return. My aim is to show that Ibn Hajar was a very successful organizer who was thus able to achieve great accomplishments both in his administrative and scholarly activities by how he perfectly operated the patronage and substitution system, while at the same time making an appraisal of Ibn Khidr and his hardly recognized efforts.